Studi Komparasi Pembagian Harta Warisan Menurut Adat Dan Hukum Islam Desa Pace Kecamatan Silo Kabupaten Jember - Abdul Halim (el-Bait: Jurnal Hukum Keluarga Islam, 2024)
Inheritance is one of the most important world affairs, for Muslims themselves, because matters related to inheritance are one of the obligations that must be carried out as best as possible by Muslims themselves, because this shows faith and piety to Allah and His Messenger. Islam places great importance on the issue of "faraid" because inheritance is the cause of property ownership. Meanwhile, wealth is very necessary for every Muslim in this world, because wealth is one of the provisions for getting closer to Allah and is very important in household life. Talking about community or family problems certainly cannot be separated from the laws that apply in every rural area, because every village has rules or customs that have been agreed upon and implemented collectively. Pace village in dividing inheritance is not based on Islamic inheritance law, and chooses customary law in settling the distribution of inheritance, where there are many conflicts between the two laws. Therefore, it is very necessary to carry out careful research in order to know correctly about the inheritance laws that exist in Pace village, Silo sub-district, Jember Regency. The aim of this research is to find out what the inheritance distribution system is like in Pace village, Silo sub-district, Jember regency. and What is the impact of the customary inheritance distribution system in the perspective of Islamic law? For this purpose, researchers used qualitative methods to collect the required data, such as: observation, interviews and documentation. From the results of the research carried out, the distribution of inherited assets is generally carried out based on custom. Where the share of each child, whether male or female, is basically the same as agreed between the other heirs and the basis for the distribution is harmony and togetherness and taking into account the special circumstances of each heir. From the process of dividing inheritance, it turns out that it does not conflict with Islamic law, in the sense that it is permissible because it is considered a custom that does not conflict with Islamic law, because it is carried out using a system of principles of justice and balance as well as agreement and willingness in the sense of men and women getting their rights. rights that are commensurate with their respective obligations in family and community life.